Double-sided nanowire array film

By combining the bilateral copper nanowire array with viscous polymer to make a nanostructure composite thermal interface (NCTI), the problem of difficult to take into account the thermal conductivity and mechanical softness of existing thermal interface materials, and efficient thermal and Electricity management.

CN119404287APending Publication Date: 2025-02-07CARNEGIE MELLON UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047621.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-13
Filing Date
2023-05-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing thermal interface materials are difficult to balance between thermal conductivity and mechanical flexibility, resulting in inefficient thermal management, especially in heterogeneous integration, high thermal interface resistance becomes a bottleneck.

Method used

A nanostructured composite thermal interface (NCTI) made of a combination of a separate two-sided copper nanowire array and a viscous polymer is used to penetrate the polymer layer through the nanowires and directly contact the surface of the target object, forming an efficient thermal and current channel.

Benefits of technology

It achieves high superconductivity (more than 100W/m-K) and high conductivity, and has high mechanical compliance, adapts to thermal stress, and significantly reduces thermal interface resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404287A_ABST
    Figure CN119404287A_ABST
Patent Text Reader

Abstract

A nanostructured composite thermal interface and a method of making the interface are disclosed. The interface is composed of a metal foil having an array of metal nanowires disposed on either side thereof. A viscous polymer is interspersed within the nanowires in each array and acts as an adhesive to bond the interface to a surface of a target object, such as a CPU and a heat sink.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 341,758, filed on May 13, 2022, the contents of which are incorporated herein in their entirety. Background Art

[0003] Effective heat dissipation is important for energy-efficient and safe operation in energy-intensive devices and systems. Existing data centers consume about 200 terawatt hours (TWh) per year, which will continue to grow with the development of cloud computing and artificial intelligence. Cooling accounts for 33-40% of data center energy use and consumes billions of tons of water each year. The heat flux of high-power electronic devices such as solid-state lasers, wide-bandgap transistors, and phased array radars has reached an unprecedented level of ~1 kW / cm 2 , which, without effective thermal management, will lead to rapid device performance and lifetime degradation.

[0004] With heterogeneous integration becoming increasingly inevitable and common in electronic devices and systems, thermal interface resistance, which can constitute more than 50% of the total thermal resistance, has become a bottleneck in thermal management. To thermally bridge and mechanically connect interfaces, thermal interface materials (e.g., greases, compounds, pads, tapes, solders, and epoxies) have been used.

[0005] However, developing high-performance thermal interface materials remains a significant challenge because it must be both thermally conductive and soft to simultaneously reduce thermal interface resistance and accommodate thermal stress.

[0006] Thermal greases, compounds and epoxies have high conformability, but they have low thermal conductivity. Solders have high thermal conductivity, but have the disadvantages of low mechanical conformability, require high temperature soldering processes, and are not suitable for joining large parts, which significantly hinders their application as universal joints.

[0007] Arranged or ordered nanostructures including carbon nanotubes (CNTs), nanowires, graphene, nanosheets, and nanofibers are promising for making thermally conductive and mechanically soft thermal interface materials. However, the fabrication of these nanostructures is usually expensive and not scalable. In addition, most of these nanostructures are not adhesive or weldable and rely mainly on pure dry heat contact with the substrate, which largely compromises their performance. Summary of the invention

[0008] A novel nanostructured composite thermal interface (NCTI) and a method for making the NCTI are disclosed. In one embodiment, the NCTI consists of a free-standing double-sided copper nanowire (CuNW) array combined with an adhesive polymer to produce a double-sided copper nanowire-polymer composite film. The film can be used as an adhesive, high-performance, paper-like thermal and electrical interface material. The copper nanowire array is grown from the bottom up on both sides of a thin copper foil and then coated with an adhesive polymer.

[0009] When used to join two objects, the nanowires penetrate the coated soft polymer layer with a slight pressure to make direct contact to adapt to the surface morphology of the object, acting as an effective heat and current channel. At the same time, the high-conductivity copper foil in the middle acts as a thermal / electrical regulator, and the sticky polymer provides a strong bond to join the interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] By way of example, certain exemplary embodiments of the disclosed systems and methods will now be described with reference to the accompanying drawings, in which:

[0011] Figure 1 The formation of NCTI is schematically illustrated, where the double-sided nanowire array film acts as a conductive and compliant scaffold, and the adhesive tightly bonds the NCTI to the mating surface and maintains structural integrity after curing.

[0012] Figure 2 SEM images of the cross section of the NCTI bonding joint and the actual interface with a three-layer structure are schematically shown.

[0013] Figure 3 Schematic diagram showing the conformity of the nanowires to the surface morphology of the target object to directly contact the target object, thereby forming an effective vertical heat flow channel through the interface, and SEM image showing the top view of the nanowires penetrating the viscous polymer layer to directly contact the substrate surface.

[0014] FIG. 4 schematically illustrates steps in the fabrication of the NCTI disclosed herein.

[0015] Figure 5 is a SEM image of a double-sided nanowire array without an adhesive polymer layer.

[0016] Figure 6 The setup of NCTI between two target objects is shown.

[0017] Figure 7 is a SEM image showing a cross-sectional view of a double-sided nanowire array without a polymer layer.

[0018] Figure 8is a SEM image showing a cross-sectional view of a double-sided nanostructured composite film with embedded resin.

[0019] Figure 9 shows the thermal and mechanical properties of NCTI. (A) is a schematic diagram showing the half sample and thermal resistance composition for frequency domain thermal reflectivity (FDTR) measurements. (B) is a typical FDTR data plot and the best least squares fit to the heat transfer model; the inset shows multiple test points. (C) is a summary of R NW-树脂 / obj and k NW-树脂 Histograms of (a) and (b) extracted from FDTR measurements at different test points. (D) is a histogram showing the composition of the total thermal resistance dominated by the CuNW / resin composite layer (75.3%). (E) is a graph showing the stiffness characterization of an isolated CuNW bundle using in-situ cylindrical flat punch indentation monitored under SEM; the inset shows the SEM image of the nanoindentation method. (F) is a graph showing the tensile strength test of two copper parts bonded by NCTI (blue) and neat AB resin (orange), respectively, showing comparable bonding strengths; the inset shows an image of the tested sample.

[0020] Fig. 10A The diagram schematically shows NCTI applied between a CPU and a cooler in a computer.

[0021] Fig. 10B It is more about using NCTI as thermal interface material Fig. 10A Graph of CPU operating temperature with the use of thermal paste as thermal interface material. Specific implementation plan

[0022] A scalable, low-cost nanostructured composite thermal interface (NCTI) is disclosed and, in one embodiment, fabricated by combining free-standing double-sided copper nanowire (CuNW) arrays with an adhesive polymer.

[0023] When used to join two objects, the nanowires penetrate the coated soft polymer layer to make direct contact with the surface of the target object through slight pressure and adapt to the surface morphology of the target object so that the NCTI acts as an effective heat and current channel. At the same time, the highly conductive copper foil between the nanowire arrays acts as a thermal / electrical regulator, and the sticky polymer provides a strong bond to join the interface.

[0024] Based on this permeable metal nanowire scaffold, NCTI exhibits an ultra-high thermal conductivity of over 100 W / mK, which is two orders of magnitude higher than the thermal conductivity of composite epoxy resins (~1 W / mK) and one order of magnitude higher than the thermal conductivity of solder (~10 W / mK). NCTI also has a high electrical conductivity similar to that of metals, and its electrical conductivity is empirically found to be about one order of magnitude higher than that of commercial double-sided copper tape.

[0025] In addition to high thermal and electrical conductivity, NCTI also has high mechanical compliance. Both the high aspect ratio copper nanowire array and the adhesive polymer are soft in order to accommodate thermal stresses arising from possible mismatches in the thermal expansion coefficients of the joined objects.

[0026] Unrestricted by scale, this adhesive, high-performance paper-like interface film can be directly applied to the bonding of two target objects with slight pressure at room temperature, providing excellent heat dissipation and electrical conductivity.

[0027] Figure 1 The formation of NCTI is schematically illustrated, where the double-sided nanowire array acts as a conductive and compliant scaffold, and the adhesive polymer tightly bonds the NCTI to the mating surface of the target object and maintains the structural integrity after curing. Figure 2 A perspective view of the three-layer structure of the NCTI-bonded joint is schematically shown, and the SEM image shows a cross-sectional view of the actual interface. Figure 3 A side view of the same interface is shown, and the SEM image shows a top view of the NCTI, showing that the metal nanowires penetrate the viscous polymer layer to directly contact the surface of the target object.

[0028] FIG4 shows one possible method for producing the NCTI described herein. In step (a), templates 404a, 404b are attached to opposite sides of a metal foil 402. The templates 404a, 404b are preferably commercially available sheets having holes defined therein through which the nanowires are grown. In one instance, the templates may be made of a polycarbonate material.

[0029] In a preferred embodiment, the metal foil 402 is a copper foil, which may be between about 1 μm and 100 μm thick, and is preferably about 10 μm thick, but other metals may be used in variations. In step (b), the nanowires 406 are preferably deposited by electrochemical deposition, but other methods may also be used. The deposition results in the growth of a vertically aligned array of nanowires 408 on both sides of the metal foil 402. In a preferred embodiment, the nanowires are composed of copper, but in variations, other metals may be used.

[0030] In some embodiments, nanowires can be grown by immersing the foil in an electrolyte bath, wherein the electrolyte comprises, for example, copper sulfate. Other electrolytes can be used when growing nanowires composed of materials other than copper. In the case where the surface of the target object is irregular or curved, conformal NCTIs can be produced according to the methods disclosed in co-pending patent application PCT / US2023 / 021452, entitled "Growth of Vertically-Aligned Nanowires on Conductive Surfaces," the contents of which are incorporated herein in their entirety.

[0031] In various embodiments, the diameter of the nanowires varies between 10 nm and 30 μm, but is preferably in the range of 50-1000 nm. In various embodiments, the height of the nanowires varies between about 5 μm and 100 μm, but is preferably in the range of 20 μm to 50 μm. In various embodiments, the nanowires cover 5% to 50% of the surface area of ​​the metal foil base. Other diameters, heights, diameter / height ratios, and packing ratios may be used depending on the application.

[0032] In step (c) of the method, the templates 404a, 404b are removed by chemical dissolution.In step (d) of the process, the top of the nanowire array 408 is coated with a sticky polymer layer 410. Figure 5 is an image showing a double-sided nanowire array before applying a viscous polymer. Preferably, the viscous polymer has a viscosity of less than or equal to 10,000 cP. In one embodiment, the viscous polymer can be Epoxy Set #145-20005, 100:12, mixed with hardener #145-20010, with a viscosity of 300 cP, manufactured by Allied High Tech Products Inc. of Ceritos, California. Other equivalent products can be used.

[0033] Figure 6 The process of mating the NCTI with the target objects 602a, 602b is shown. The NCTI 604 is placed between the surfaces of the target objects 602a, 602b, and a slight pressure is applied. The pressure forces the viscous polymer 410 between the nanowires 406 of the nanowire array 408. The applied pressure causes the nanowires 406 to penetrate the viscous polymer layer and contact the surface of the target objects 602a, 602b, which significantly contributes to the high thermal and electrical properties of the material. Preferably, the required pressure is less than or equal to 1000 psi.

[0034] Figure 2A second image of an actual NCTI according to the present disclosure is shown, showing the sticky polymer coating the nanowires. Figure 6 is similar to the schematic diagram shown in the inset of . Figure 3 The inset shows the top of the nanowire penetrating the sticky polymer layer to allow contact with the surface of a target object (not shown).

[0035] In some embodiments, the double-sided nanowire array 408 is used together with the central Cu substrate layer 402 as a conductive and compliant scaffold due to the high thermal conductivity of copper and the high aspect ratio (>100) of the nanowires 406. In some embodiments, the adhesive polymer layer can be a low-viscosity adhesive (e.g., resin, epoxy, strong adhesive, etc.), the application of which will result in strong capillary forces caused by the high surface energy of the nanowire array 408 and the adhesive polymer 410, thereby allowing a tight bonding of the nanostructure scaffold to the mating surface of the target object, as previously described. It should be noted that one advantage of NCTI is that it allows room temperature bonding compared to soldering processes performed at much higher temperatures (typically >200°C). This allows for a wider range of applications in various environments and materials.

[0036] In some embodiments, the compliance of the nanowire array is important to ensure that the nanowires conform to the substrate morphology of the surface of the target object and directly contact the surface to form an effective vertical heat flow channel across the interface before the adhesive is cured. In some embodiments, the high thermal conductivity base layer 402 (i.e., copper foil in the preferred embodiment) between the nanowire arrays 408 is used as a lateral thermal regulator for collecting and spreading heat, such as Figure 3 As shown, resulting in increased heat flux uniformity. In some embodiments, NCTI can synergistically regulate heat flow in both out-of-plane and in-plane directions along the interface, which is an important advantage over vertically aligned CNTs, nanowires, and nanofibers. In some embodiments, after the adhesive is cured, the contact between the nanowires and the mating substrate can be fixed and anchored without applying any external pressure, thus providing strong interfacial bonding and resilience to thermal cycling and vibrations, compared to pure dry contact.

[0037] Figure 7 is a SEM image showing a cross-sectional view of a double-sided nanowire array without polymer, and Figure 8 is a SEM image showing a cross-sectional view after the polymer has been applied.

[0038] In practical applications, it is important to measure the thermal transport properties of NCTI and the thermal interface resistance between NCTI and the substrate. The frequency domain thermoreflectance (FDTR) method can be used to measure the thermal transport properties of NCTI. Fig.9AAs shown in Figure 2, the FDTR method is a pump-probe optical technique, where a modulated pump beam excites the sample while a probe beam measures the temperature-dependent reflectivity change. The phase lag between the pump laser and the probe laser can be measured as a function of the modulation frequency, where the thermal properties of the sample, including in-plane and cross-plane thermal conductivity and thermal interface resistance, can be extracted by fitting the measured data to a 2D thermal conduction model of the multilayer film. Due to the symmetry of NCTI, one half of the thermal interface can be characterized, such as Fig.9A As shown, samples can be fabricated using a resin as a sticky polymer and bonding the nanowires to a Cu substrate.

[0039] In Figure 9 (BD), FDTR measurements can be performed at 9 different locations on the sample from both sides (half of the NCTI). When using resin as the adhesive polymer, the average thermal conductivity of the 25 μm thick CuNW / resin composite was measured to be 71.6 ± 14.1 W / mK, corresponding to 0.349 ± 0.069 mm 2 ·K / W thermal resistance. For comparison, the measured thermal conductivity of the 10μm Cu-substrate layer in the middle of the NCTI can be 376.6±37.7Wm·K. The thermal interface resistances of the CuNW-resin / substrate and CuNW-resin / Cu-substrate interfaces can be measured to be 0.075±0.013mm 2 K / W and 0.027±0.005mm 2 Based on these FDTR measurements, by assuming that the NCTI can be symmetrically bonded between two Cu substrates, the total thermal resistance of the NCTI in the fully bonded sample (including the thermal interface resistance) can be estimated to be 0.928 ± 0.140 mm 2 ·K / W.

[0040] like Fig.9D As shown in Figure 5, the CuNW / resin composite layer can generate most of the total thermal resistance (75.3%). Fig.9E In the present work, the Young's modulus of the nanowire array (d = 200 nm) was characterized as ~2.5 GPa by in situ cylindrical flat punch (d = 10 μm) indentation, which is two orders of magnitude lower than that of bulk copper. Therefore, this soft structure allows for strong morphological compliance under slight external pressure during bonding. The bonding strength of the CuNW-resin can be measured and compared with that of the neat resin, as shown in Figure 2. Fig.9F The maximum allowable load of CuNW-resin can be measured to be 207.6N, which is 2 The bonding area shows a strong bonding strength comparable to that of pure resin (255.5N).

[0041] Also tested NCTI on the CPU for actual cooling test, such as Fig. 10AAs shown schematically, the NCTI 604 is shown disposed between a CPU 1102 and a heat sink 1104 equipped with a cooling fan 1106. An open desktop computer equipped with a 65W standard office-grade CPU 1102 and an air cooler was assembled as a test platform. Fig. 10B The cooling performance of NCTI is illustrated in FIG. The performance of NCTI is evaluated by monitoring the temperature of CPU 1102 under full load using its built-in temperature sensor and benchmarking it with a commercial thermal paste at the same thickness of 60 μm. Fig. 10B As can be seen in the graph in , the thermal paste allows the CPU 1102 to operate stably at full load at a measured temperature of ~72°C, and consumes about 70.8 W. In contrast, using NCTI, the operating temperature of the CPU 1102 is significantly reduced to ~58°C, demonstrating the excellent thermal performance of this new material.

[0042] It is noteworthy that CPU energy consumption is reduced to only about 66.6W, a considerable saving of about 4.2W (about 5.9%). In some embodiments, based on a simple and low-barrier replacement using NCTI, a more powerful CPU with significant performance improvements can be assembled on existing smart devices without increasing operating temperatures. Therefore, NCTI provides a low-cost upgrade solution for all categories of electronic devices and systems in addition to hardware upgrades, including but not limited to data centers and portable devices. On the other hand, even if all hardware remains original, NCTI can benefit the electronic device or system by allowing the electronic device or system to operate at much lower temperatures and save energy by reducing the generation of waste heat. This will be meaningful to a wide range of semiconductor devices and save a considerable amount of energy.

[0043] As will be appreciated by those skilled in the art, many variations of the implementations discussed herein that fall within the scope of the invention are possible. For example, the method may use different materials for the metal foil substrate and the nanowires. Various embodiments may have nanowires of different heights, diameters, height to diameter ratios, and packing ratios. The density of the nanowires may vary depending on the template used. The length of time used to grow the nanowires may also vary depending on the application. Finally, various embodiments may use different materials as the adhesive polymer. Many variations to the NCTI arrays fabricated and the fabrication process are possible and are considered to be within the scope of the invention.

[0044] In addition, it should be understood that the features of the various embodiments described herein are not mutually exclusive and may exist in various combinations and arrangements without departing from the spirit and scope of the present invention, even if such combinations or arrangements are not explicitly made herein. Therefore, the exemplary devices and methods disclosed herein should not be considered as limitations of the present invention, but as illustrations thereof. The scope of the present invention is defined by the appended claims.

Claims

1. A nanostructured interface comprising: Conductive films or foils; as well as Conductive nanowire arrays are disposed on both sides of a conductive film or foil.

2. The nanostructured interface according to claim 1, further comprising: A sticky polymer is dispersed within the nanowires in each array, forming a composite film.

3. The nanostructured interface of claim 1, wherein the nanowires are brought into contact with the surface of the object by extrusion of additional adhesive polymer.

4. The nanostructured interface of claim 1, wherein the metal foil and the nanowires are comprised of copper.

5. The nanostructured interface of claim 1, wherein the diameter of the nanowires is between 10 nm and 30,000 nm.

6. The nanostructured interface of claim 1, wherein the nanowires have a height between 5 μm and 100 μm.

7. The nanostructured interface of claim 1, wherein the nanowires cover 5% to 50% of each side of the metal foil.

8. The nanostructured interface of claim 1, wherein the metal foil has a thickness between 1 μm and 100 μm.

9. The nanostructured interface of claim 2, wherein the viscous polymer is a low viscosity resin or glue or epoxy resin.

10. The nanostructured interface of claim 2, wherein the composite film is bonded to a surface of a target object after the adhesive polymer is cured.

11. A method comprising: providing a conductive foil; attaching templates to opposing sides of the metal foil, the templates each defining a plurality of holes therein; growing thermally conductive nanowires through the holes of the template to produce nanowire arrays on opposing sides of the foil; as well as The template is dissolved.

12. The method according to claim 11, further comprising: The thermally conductive nanowire array is coated with an adhesive polymer to form a composite film.

13. The method according to claim 12, further comprising: placing the composite film between surfaces of two target objects; applying pressure to force the viscous polymer to fill spaces between the nanowires of each nanowire array; as well as The adhesive polymer is cured to bond the composite film to the surface of the target object.

14. The method of claim 13, wherein the applied pressure causes the tips of the metal nanowires to contact the surface of the target object.

15. The method of claim 11, wherein the metal foil and the nanowires are comprised of copper.

16. The method of claim 12, wherein the viscous polymer is a low viscosity resin or glue or epoxy.

17. The method of claim 11, wherein the diameter of the nanowires is between 10 nm and 30,000 nm.

18. The method of claim 11, wherein the height of the nanowires is between 5 μm and 100 μm.

19. The method of claim 11, wherein the nanowires cover 5% to 50% of each side of the conductive foil.

20. The method of claim 11, wherein the conductive foil has a thickness between 1 μm and 100 μm.

21. The method of claim 12, wherein the viscous polymer has a viscosity less than or equal to 10,000 cP.

22. The method of claim 13, wherein the applied pressure is less than or equal to 1000 psi.